Imagens e memórias de atingidos por barragem: contribuições para políticas públicas sociais no reassentamento Cajá de Itatuba – PB - Barbosa, Givanilton de Araújo (2021)
This dissertation aimed to approximate the visual anthropology and the social and public policies. An approach to the collective memory of a community affected by a dam is introduced. This community is currently known as agrovillage or resettlement in Sítio Cajá, Municipality of Itatuba, in the scrubland of Paraíba. The general objective of this dissertation is to research visual and oral memories of the riverside territory in articulation with the resettled community, supported by the People Affected by Dams Movement. Based mostly on documents, photographs, audiovisual materials and oral reports, this research sought to reconstruct the Sítio Cajá’s recent history, through a long-standing relationship established between 14 local families with the researcher, whose family also once belonged to the former community. For that reason, this study was carried out using qualitative methodologies, combining open interview techniques and life stories, analyses of photos and videos, nethnography and autoethnography. This work intends to deal with local memories due to the territorial reconfiguration caused by the resettlement, while it analyzes the implementation of the Acauã Dam as a water security policy in the state of Paraíba, aligned with the national development project. Finally, this study demonstrates that the resettled community demands were only met with the Public Ministry’s assistance, and even so, after 20 years, some issues to implement social and public policies at the area still remain. Some of the several issues caused by the resettlement are the observation of family separation, restrictions on agriculture, poultry and animal husbandry activities, and Farmers’ Association disengagement. The formation of an ethnographic collection with hundreds of photographs is added to this dissertation, as ways to subsidize the rights of Sítio Cajá’s inhabitants to recollection, to those affected by the Acauã dam.